Radio direction finding and superresolution - Gething, P. J. D. (London, United Kingdom Institution of Engineering and Technology, 1991)
The book reviews developments in the following fields: ionospheric modes; wave-field models; zero-aperture bearings in two-ray wave-fields; directive array patterns; instrumental and site errors; wave interference effects for circular arrays; wave interference effects for interferometers; wavefront analysis; superresolution algorithms; ray paths; ionospheric tilts; and bearing accuracy and DF plots.
Revised edition of: Radio direction-finding and the resolution of multicomponent wave-fields.
Electronic reproduction.
Keywords: Radio direction finders; Radio waves; Electronic books